2021
DOI: 10.3390/jimaging7090171
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficacy of Handcrafted and Deep Features for Seed Image Classification

Abstract: Computer vision techniques have become important in agriculture and plant sciences due to their wide variety of applications. In particular, the analysis of seeds can provide meaningful information on their evolution, the history of agriculture, the domestication of plants, and knowledge of diets in ancient times. This work aims to propose an exhaustive comparison of several different types of features in the context of multiclass seed classification, leveraging two public plant seeds data sets to classify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…No image construction was required, and no complex neural networks needed to be trained. In the literature, several works have also shown that handcrafted features can achieve comparable performance to deep learning approaches with the former having the merit of reduced computational complexity which could be attractive in real-time applications [ 106 , 107 , 108 ]. Another advantage of the presented method is that unlike in other literature where all the frequency bands or the raw EEG signal were considered, only the alpha band was used for feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…No image construction was required, and no complex neural networks needed to be trained. In the literature, several works have also shown that handcrafted features can achieve comparable performance to deep learning approaches with the former having the merit of reduced computational complexity which could be attractive in real-time applications [ 106 , 107 , 108 ]. Another advantage of the presented method is that unlike in other literature where all the frequency bands or the raw EEG signal were considered, only the alpha band was used for feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al [30] also exploited TL strategies using both natural and medical images and performed an extensive test of some off-the-shelf CNNs to realise a binary classification. Some other techniques not explored in this work are based on the combination of CNNextracted features and handcrafted ones [31][32][33] or the direct use of object detectors [34]. For example, Kudisthalert et al [33] proposed a malaria parasite detection system, based on the combination of handcrafted and deep features, extracted from pretrained AlexNet.…”
Section: Related Workmentioning
confidence: 99%
“…Some other techniques not explored in this work are based on the combination of CNN-extracted features and handcrafted ones [ 31 , 32 , 33 ] or the direct use of object detectors [ 34 ]. For example, Kudisthalert et al [ 33 ] proposed a malaria parasite detection system, based on the combination of handcrafted and deep features, extracted from pretrained AlexNet.…”
Section: Related Workmentioning
confidence: 99%
“…Non-handcrafted features can be extracted using the compact binary descriptor (CBD), convolutional neural networks (CNN), or principal component analysis network (PCAN) [ 29 – 31 ]. In particular, CNN-based deep features are robust and efficient compared to the handcrafted features [ 18 , 29 , 32 ], due to their independence of prior knowledge and image extraction and applicability to any images. However, non-handcrafted features have the following limitations: (a) The interpretability of non-handcrafted features is low, which means that it is difficult to describe the learned features [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%